The child and Adolescent Trauma Screen 2 (CATS-2) – validation of an instrument to measure DSM-5 and ICD-11 PTSD and complex PTSD in children and adolescents. Issue 2 (19th December 2022) - Sachser, Cedric; Berliner, Lucy; Risch, Elizabeth; Rosner, Rita; Birkeland, Marianne S.; Eilers, Rebekka; Hafstad, Gertrud S.; Pfeiffer, Elisa; Plener, Paul L.; Jensen, Tine K.
ABSTRACT: Background: The study examined the psychometric properties of the Child and Adolescent Trauma Screen 2 (CATS-2) as a measure of posttraumatic stress disorder (PTSD) according to DSM-5 and (Complex) PTSD following the ICD-11 criteria in children and adolescents (7–17 years). Methods: Psychometric properties were investigated in an international sample of traumatized children and adolescents ( N  = 283) and their caregivers ( N  = 255). We examined the internal consistency (α), convergent and discriminant validity, the factor structure of the CATS-2 total scores, latent classes of PTSD/Complex PTSD (CPTSD) discrimination, as well as the diagnostic utility using ROC-curves. Results: The DSM-5 total score (self: α = .89; caregiver: α = .91), the ICD-11 PTSD total score (self: α = .67; caregiver: α = .79) and the ICD-11 CPTSD total score (self: α = .83; caregiver: α = .87) have proven acceptable to excellent reliability. The latent structure of the 12-item ICD-11 PTSD/CPTSD construct was consistent with prior findings. Latent profile analyses revealed that ICD-11 CPTSD was empirically distinguishable from ICD-11 PTSD using the CATS-2. ROC-analysis using the CAPS-CA-5 as outcome revealed that CATS-2 DSM-5 PTSD scores of ≥21 (screening) to ≥25 (diagnostic) were optimally efficient for detecting probable DSM-5 PTSD diagnosis. For the ICD-11 PTSD scale scores of ≥7 (screening) to ≥9 (diagnostic) were optimally efficient for detecting probable DSM-5 PTSD diagnosis. Conclusions: The CATS-2 is a brief, reliable and valid measure of DSM-5 PTSD, ICD-11 PTSD and CPTSD symptomatology in traumatized children and adolescents, allowing crosswalk between diagnostic systems using one measure. HIGHLIGHTS: The CATS-2 screens for potentially traumatic events (PTEs) and PTSD symptoms. The CATS-2 captures DSM-5 and ICD-11 criteria for PTSD and CPTSD and enables clinicians and researchers to crosswalk between both diagnostic systems. International validation has proven good psychometric properties and presents cut-off scores The CATS-2 is a license-free instrument and is freely accessible.